Pseudomonas aeruginosa as a potential cause of antibiotic-associated diarrhea. - Kim, S. W. (Korean Academy of Medical Sciences, 2001)
Although Pseudomonas aeruginosa is not generally considered as a cause of antibiotic-associated diarrhea, several cases of diarrhea caused by P. aeruginosa have been reported. We experienced seven cases of nosocomial diarrhea presumably caused by P. aeruginosa, which was the predominant organism isolated from stool cultures. Clostridium difficile toxin was also positive in one patient. No other potential or recognized enteropathogens were identified from stools. All patients had underlying diseases and had been receiving antibiotics before the diarrheal onset. All of the seven P. aeruginosa isolates were resistant to previously given antibiotics. Diarrhea stopped three days after withdrawal of probable offending antibiotics without specific treatment in two patients. The other five patients having continuous diarrhea despite withdrawal of probable offending antibiotics, were successfully treated with antipseudomonal agents. The median duration of diarrhea after the initiation of treatment was 6.3 days. These data suggest that P. aeruginosa can be a potential cause of antibiotic-associated diarrhea. Further investigations are warranted to evaluate the possible etiologic role of P. aeruginosa in antibiotic-associated diarrhea.